Association of Clostridioides difficile with adverse clinical outcomes in patients with acute diverticulitis: A nationwide study. Issue 4 (10th September 2020) - Makar, Michael; Makar, Gabriel; Xia, Weiyi; Greenberg, Patricia; Patel, Anish Vinit
Abstract: Background and Aim: Acute diverticulitis (AD) is a common gastrointestinal disease with a significant health care‐associated burden. Patients hospitalized with AD have many risk factors for developing Clostridioides difficile infection (CDI). CDI is associated with poor outcomes in many diseases but has yet to be studied in AD. Methods: We utilized data from the National Inpatient Sample from January 2012 to October 2015 for patients hospitalized with AD and CDI compared with AD alone. Primary outcomes, which were mortality, length of stay, and hospitalization cost, were compared. Secondary outcomes were complications of diverticulitis and need for surgical interventions. Risk factors for mortality in AD and risk factors associated with CDI in AD patients were analyzed. Results: Among 767 850 hospitalizations for AD, 8755 also had CDI. A propensity score‐matched cohort analysis demonstrated that CDI was associated with increased risk of inpatient mortality (odds ratio [OR] 2.78, 95% confidence interval [CI] 1.30, 5.95), prolonged duration of hospitalization by 4.27 days ( P  < 0.0001), total hospital cost by $33 271 ( P  < 0.0001), need for surgery (OR 1.45, 95% CI 1.22, 1.71), and complications of diverticulitis (OR 1.45, 95% CI 1.21, 1.74). Predictors of CDI among patients with AD included female gender (1.12 OR, 95% CI 1.01, 1.24), three or more comorbidities (1.81 OR, 95% CI 1.57, 2.09), and admissions to teaching hospitals (1.44 OR, 95% CI 1.22, 1.70). Conclusions: Clostridioides difficile infection in AD is associated with increased mortality, length of stay, and hospital cost. Preventative measures should be made for at‐risk patients with AD to decrease infection rate and poor outcomes.